2019
DOI: 10.1111/cge.13556
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing and variant discovery in the ASPIRE autism spectrum disorder cohort

Abstract: Autism spectrum disorder (ASD) is a highly heterogeneous genetic disorder with strong evidence of ASD‐association currently available only for a small number of genes. This makes it challenging to identify the underlying genetic cause in many cases of ASD, and there is a continuing need for further discovery efforts. We sequenced whole genomes of 119 deeply phenotyped ASD probands in order to identify likely pathogenic variants. We prioritized variants found in each subject by predicted damage, population freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
(86 reference statements)
0
15
0
Order By: Relevance
“…Variants in CAMTA1 have also been reported in several large screening studies in undiagnosed patients with developmental disorders 18,21,30,31 and ASDs, 22 but with limited clinical data. Supplementary Table 4 gives an overview of these patients with their associated phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variants in CAMTA1 have also been reported in several large screening studies in undiagnosed patients with developmental disorders 18,21,30,31 and ASDs, 22 but with limited clinical data. Supplementary Table 4 gives an overview of these patients with their associated phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…All patients showed nonprogressive congenital ataxia with or without ID 16 . Subsequent studies reported on additional heterozygous intragenic rearrangements 17,18 as well as missense and truncating variants 18‐22 . Clinical heterogeneity was observed, even within the same family, with various predominant phenotypes including ataxia and/or spasticity, tremor, and developmental delay (DD) and/or ID 16,17,19,20 …”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the range of PTEN protein function existing in the general population, 8 variants were selected based on their relatively high frequency in the gnomAD database 23 , termed Population Variants. Additionally, variants were included with either Predicted High Impact (17) or Predicted Low Impact (5) as determined by CADD phred version 1.0 24 or SNAP2 scores 25 . We also included 2 NS mutations, R130X and R335X, due to their common association with ASD, PHTS and somatic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Headway in understanding ASD pathophysiology has been stymied by tremendous phenotypic heterogeneity and complex genetics across individuals. Conclusively linking genes to ASD is challenging since sequencing efforts have identified mutations in hundreds of genes from individuals with the disorder [2][3][4][5][6][7] . Confidence of gene association to ASD is enhanced by identification of de novo, likely gene disrupting (LGD) mutations; however, the most common de novo mutations identified in individuals with ASD are missense (MS) variants of unknown significance (VUS) 2,7 .…”
mentioning
confidence: 99%
“…Werling and co-workers [ 70 ] observed a median of 64 de novo single nucleotide variants (SNVs) and 5 de novo indels per child across autosomes.No significant enrichments were observed for either de novo or rare inherited structural variants (SVs), though this study detected 171 de novo SVs [ 70 ]. Five predicted high-impact variants as de novo were detected in WGS data on 119 individuals [ 71 ] along with two novel de novo variants in the ASD gene SCN2A.…”
Section: Genetics Studiesmentioning
confidence: 99%